Implementation of the Support Vector Machine Method for Sentiment Analysis Using Twitter Data - Widya Wahyuni (Knowbase : International Journal of Knowledge in Database, 2022)
The development of feminism, which is centered on women all over the world who want to be free of male pressure, oppression, and inequality, has continued to the present day. Various public opinions about feminism are now being expressed on various social media platforms. There has been a long debate about feminism's critics and supporters in terms of equalizing women's intellectual and the role of women in making decisions. Not only that, but the desire to end acts of violence and injustice against women is a form of feminism that is often taken for granted, even in the legal realm. The purpose of this study was to examine public sentiment based on opinions shared on social media. Hashtags related to feminism from social media are the main data that will be used to analyze public opinion sentiments about feminism. In this study, 500 tweets were used, and the data was later separated into positive, negative, and neutral opinions before being analyzed using the Support Vector Machine (SVM) method. The results of this study obtained an accuracy of 72%, indicating that the use of SVM to perform sentiment analysis on Twitter data is quite good.